Analysis of the readiness of tempe UMKM UD. Bismillah in implementing fixed financial accounting standards in Delitua District - Atika Arif; Tri Inda Fadhila Rahma; Hendra Hermain (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the level of readiness of Tempe MSME UD. Bismillah in implementing Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in Delitua District. The implementation of SAK ETAP is an effort to improve the quality of MSME financial reports to make them more relevant, reliable, and acceptable to stakeholders, especially in terms of access to financing and business transparency. The research method used is a qualitative approach with a case study design. Data collection techniques were carried out through in-depth interviews, direct observation, and documentation of accounting practices carried out by business actors. The results of the study indicate that Tempe MSME UD. Bismillah is in the early stages of readiness, with a financial recording system that is still simple and does not refer to the principles of SAK ETAP. The main factors inhibiting the implementation of this standard include low accounting literacy, limited human resources, and the less-than-optimal role of supporting agencies such as the cooperative and MSME office. However, there is potential for development through increasing the willingness of business actors to learn and receive mentoring. This study recommends intervention from related parties in the form of technical training, provision of SAK ETAP modules tailored to the characteristics of MSMEs, and the establishment of a sustainable mentoring program so that the implementation of SAK ETAP can be realized gradually.